Use mathematical induction to prove the property for all positive integers n.
For the equation: [a^n]^5=a^(5n)
This makes no sense to me at all.
For the equation: [a^n]^5=a^(5n)
This makes no sense to me at all.
-
First show that it is true for n=1.
[a^1]^5 = a^5
a^(5*1) = a^5
So it is true for n=1.
Now let's show that if it is true for the integer k then it is also true for k+1.
[a^(k+1)]^5
= [a^k * a]^5
= [a^k]^5 * a^5
= a^(5k) * a^5 because we said it is true for k
= a^(5k+5)
= a^[5(k+1)]
so it is true for k+1.
So, by induction, if it is true for 1, and also if it is true for a certain integer then it is also true for the next integer, it must be true for all positive integers.
[a^1]^5 = a^5
a^(5*1) = a^5
So it is true for n=1.
Now let's show that if it is true for the integer k then it is also true for k+1.
[a^(k+1)]^5
= [a^k * a]^5
= [a^k]^5 * a^5
= a^(5k) * a^5 because we said it is true for k
= a^(5k+5)
= a^[5(k+1)]
so it is true for k+1.
So, by induction, if it is true for 1, and also if it is true for a certain integer then it is also true for the next integer, it must be true for all positive integers.
-
Induction involves two steps. First you have to prove the statement is true for the base. Since n is in the positive integers, we start with n=1.
(a^1)^5 = a^5 = a^((5)(1)) = a^(5n)
So it is true for the base.
Step 2 is to assume the statement is true for 'n', and from that show that it is true for 'n+1'.
(a^n)^5 = a^(5n) <----- Assume that's true.
Now stick in 'n+1' and see what happens.
[a^(n+1)]^5 =
[(a^n)(a^1)]^5 =
[(a^n)(a)]^5
[(a^n)^5](a^5) =
[a^(5n)](a^5) = <----- Substituting what we assumed was true for (a^n)^5
a^(5n+5) =
a^(5(n+1))
And thus we have proven by mathematical induction that (a^n)^5) = a^(5n) is true for all n.
(a^1)^5 = a^5 = a^((5)(1)) = a^(5n)
So it is true for the base.
Step 2 is to assume the statement is true for 'n', and from that show that it is true for 'n+1'.
(a^n)^5 = a^(5n) <----- Assume that's true.
Now stick in 'n+1' and see what happens.
[a^(n+1)]^5 =
[(a^n)(a^1)]^5 =
[(a^n)(a)]^5
[(a^n)^5](a^5) =
[a^(5n)](a^5) = <----- Substituting what we assumed was true for (a^n)^5
a^(5n+5) =
a^(5(n+1))
And thus we have proven by mathematical induction that (a^n)^5) = a^(5n) is true for all n.
-
i guess:
first n=1
[a^1]^5=a^(5*1) true a=a
then n=k
[a^k]^5=a^(5k)
when n = k+1
[a^ (k+1)]^5=a^(5(k+1))
(a^k * a^1)^5 = (a^k)^5 * (a^1)^5 from previous expression we know that [a^k]^5=a^(5k)
substitute a^(5k) instead of (a^k)^5
a^(5k) * (a^1)^5 = a^(5k) * (a^5)^1 = a^(5k) * (a^5) = a^(5k + 5) = a^(5(k+1))
first n=1
[a^1]^5=a^(5*1) true a=a
then n=k
[a^k]^5=a^(5k)
when n = k+1
[a^ (k+1)]^5=a^(5(k+1))
(a^k * a^1)^5 = (a^k)^5 * (a^1)^5 from previous expression we know that [a^k]^5=a^(5k)
substitute a^(5k) instead of (a^k)^5
a^(5k) * (a^1)^5 = a^(5k) * (a^5)^1 = a^(5k) * (a^5) = a^(5k + 5) = a^(5(k+1))
-
[a^n]^5 = (a^n)*(a^n)*(a^n)*(a^n)*(a^n) = a^(n+n+n+n+n) = a^5n
LOL idk what induction is.
LOL idk what induction is.